EFFECTIVENESS OF INTRA OPERATIVE HAND HOLDING ON ANXIETY AND PHYSIOLOGICAL PARAMETERS AMONG PATIENTS UNDERGOING CATARACT SURGERY - S., Anuja B.; Devi, Elsa Sanatombi; Sequira, Leena; Rao, Lavanya; H., Vijaya Pai (Journal of Health and Allied Sciences NU, 2014)
Introduction: Patients who are undergoing cataract surgery under local anaesthesia may be more stressed than those having general anaesthesia as they are awake during the surgical procedure. Therefore, psychological comfort in the preoperative phase and compliance during operation are very important for postoperative prognosis. This study explored the pre operative anxiety level of patients undergoing cataract surgery and the effectiveness of intra operative hand holding on anxiety and its related physiological parameters.Methods: A quasi experimental pre-test post-test control group design was used to collect data from a purposive sample of 54 patients who were underwent cataract surgery at Kasturba Hospital, Manipal.Results: Most of the patients in the experimental group perceived intra operative hand holding as a measure to reduce their anxiety even though there was no significant statistical difference in the immediate post operative anxiety score between the groups. It was also found that hand holding was effective in reducing blood pressure and heart rate except the respiratory rate of patients undergoing cataract surgery.Conclusion: The following conclusions were drawn on the basis of the findings of the present study that is, Intra operative hand holding was effective in reducing the physiological parameters such as heart rate, systolic blood pressure and diastolic blood pressure. Also most of the patients perceived intra operative hand holding as beneficial in relieving anxiety.
Keywords: Intra operative hand holding; anxiety; physiological parameters